Pengaruh Kompensasi Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan - Mahmud Maqila; Aldo Cipta (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2023)
Employee performance is the result of work in quality and quantity achieved by an employee in carrying out their duties in accordance with the responsibilities they provide (Mangkunegara, 2009:9). The demand for high employee performance has indeed become a part of all companies. However, the current facts show that not all employees have high performance according to company expectations. There are still many employees who have low performance, as happened to Bank Jatim Surabaya employees in the initial findings in the field which showed that some employees of Bank Jatim Surabaya experienced problems related to performance as seen from not achieving targets on marketing employees.